Exploring the Evidence for an Immunomodulatory Role of Vitamin D in Juvenile and Adult Rheumatic Disease - Zou, Jiaqi; Thornton, Clare; Chambers, Emma S.; Rosser, Elizabeth C.; Ciurtin, Coziana (Frontiers in Immunology, 2021)
Vitamin D is synthesized in the skin following exposure to UVB radiation or is directly absorbed from the diet. Following hydroxylation in the liver and kidneys, vitamin D becomes its bioactive form, 1,25(OH)2D, which has been described to have potent immunomodulatory capacity. This review will focus on the effect of vitamin D in modulating the dysregulated immune system of autoimmune rheumatic diseases (ARD) patients across age, in particular in arthritis (rheumatoid arthritis and juvenile idiopathic arthritis), and systemic lupus erythematosus (with adult and juvenile onset). As well as delineating the impact of vitamin D on the innate and adaptive immune functions associated with each disease pathology, this review will also summarize and evaluate studies that link vitamin D status with disease prevalence, and supplementation studies that examine the potential benefits of vitamin D on disease outcomes. Exploring this evidence reveals that better designed randomized controlled studies are required to clarify the impact of vitamin D supplementation on ARD outcomes and general health. Considering the accessibility and affordability of vitamin D as a therapeutic option, there is a major unmet need for evidence-based treatment recommendations for the use of vitamin D in this patient population.